CT angiography of the coronary arteries (Part 2): Image analysis, reporting, case examples, position papers and new developments CT-Angiographie der Koronararterien (Teil 2): Bildanalyse, Berichterstellung, Fallbeispiele, Positionspapiere und neue Entwicklungen - von Knobelsdorff, Florian; Korosoglou, Grigorios; Hell, Michaela M.; Achenbach, Stephan; Thiele, Holger; Rolf, Andreas (Die Kardiologie, 2025)
Technical developments over the last few decades have enabled the non-invasive detailed visualization of the coronary arteries using computed tomography (CT). Coronary CT angiography (coronary CTA) enables the visualization of the coronary artery anatomy, the identification and characterization of atherosclerotic coronary plaques and the estimation of the resulting luminal stenosis. The main clinical indication for coronary CTA is the diagnostic work-up of de-novo suspected obstructive coronary artery disease (CAD). According to the most recent clinical practice guidelines issued by the European Society of Cardiology in 2024, coronary CTA is recommended if the clinical likelihood of obstructive CAD is >5–50%. Most patients with new symptoms fall into this category. The new central role of coronary CTA is based on strong evidence from large studies published in recent years. With the integration of coronary CTA into the service catalog of public health insurances in Germany from 2025 onwards, the clinical application of the method will probably expand further. To ensure a high level of quality, structured training programs and the integration of cardiological expertise into the entire process are essential: from selection of the most appropriate test and patient preparation, to CT examination and analysis up to the integration of findings into the clinical context. This article, consisting of two parts, provides a practical overview of the topic. Part 1 presents technical aspects of CT, provides information about the diagnostic performance of coronary CTA, describes the procedure for establishing the indications for coronary CTA when CAD is suspected, addresses rare indications and contraindications, summarizes the preparation and implementation of a CT examination, names certification options and provides current information for the provision of coronary CTA in outpatient care. Part 2 explains the procedure for analyzing the image data and creating a structured report, provides an image impression of coronary CTA using case studies, compiles an overview of important position papers and outlines some further developments in cardiac CT imaging.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Atherosclerosis; Computed tomography; Coronary artery disease; Myocardial infarction; Plaque